(untitled) (Fiep Bulletin - online, 2024)
Introduction: Body Dysmorphic Disorder (BDD), also known as Body Dysmorphia (BD), is characterized by an excessive and distorted preoccupation with physical appearance, leading to a negative and exaggerated perception of supposed imperfections or defects in parts of the body. Objective: To carry out a comprehensive analysis of the impact of BDD on mental health through a review of previously published systematic reviews. Methodology: Google Scholar and PubMed were used to select the studies. Keywords guided the selection of materials in both Portuguese and English. Article searches were filtered by the year 2016 to 2022, covering a six-year interval. Results: 18 systematic review studies were selected, totaling 525 studies overall. Among the studies investigated, it was noted that participants reported dissatisfaction with their body image, attempted suicide, and low self-esteem. In addition, five types of disorders that people with muscle dysmorphia may suffer from were detected: Depressive Disorders, Eating Disorders, Anxiety Disorders, Obsessive-Compulsive Disorders and Post-Traumatic Stress Disorders. Conclusion: It was found that individuals with muscle dysmorphia can cause even greater damage to their mental health, triggering even more adverse consequences. These findings highlight the need to invest in more research on this subject to promote effective intervention and prevention strategies.